Neurologic Syndromes Predict Higher In-Hospital Mortality in COVID-19. (16th March 2021) - Eskandar, Emad Nader; Altschul, David J.; de la Garza Ramos, Rafael; Cezayirli, Phillip; Unda, Santiago R.; Benton, Joshua; Dardick, Joseph; Toma, Aureliana; Patel, Nikunj; Malaviya, Avinash; Flomenbaum, David; Fernandez-Torres, Jenelys; et al.
Abstract : Objective: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is protean in its manifestations, affecting nearly every organ system. However, nervous system involvement and its effect on disease outcome are poorly characterized. The objective of this study was to determine whether neurologic syndromes are associated with increased risk of inpatient mortality. Methods: A total of 581 hospitalized patients with confirmed SARS-CoV-2 infection, neurologic involvement, and brain imaging were compared to hospitalized non-neurologic patients with coronavirus disease 2019 (COVID-19). Four patterns of neurologic manifestations were identified: acute stroke, new or recrudescent seizures, altered mentation with normal imaging, and neuro-COVID-19 complex. Factors present on admission were analyzed as potential predictors of in-hospital mortality, including sociodemographic variables, preexisting comorbidities, vital signs, laboratory values, and pattern of neurologic manifestations. Significant predictors were incorporated into a disease severity score. Patients with neurologic manifestations were matched with patients of the same age and disease severity to assess the risk of death. Results: A total of 4, 711 patients with confirmed SARS-CoV-2 infection were admitted to one medical system in New York City during a 6-week period. Of these, 581 (12%) had neurologic issues of sufficient concern to warrant neuroimaging. These patients were compared to 1, 743 non-neurologic patients with COVID-19 matched for age and disease severity admitted during the same period. Patients with altered mentation (n = 258, p = 0.04, odds ratio [OR] 1.39, confidence interval [CI] 1.04–1.86) or radiologically confirmed stroke (n = 55, p = 0.001, OR 3.1, CI 1.65–5.92) had a higher risk of mortality than age- and severity-matched controls. Conclusions: The incidence of altered mentation or stroke on admission predicts a modest but significantly higher risk of in-hospital mortality independent of disease severity. While other biomarker factors also predict mortality, measures to identify and treat such patients may be important in reducing overall mortality of COVID-19.